Mixed Dentition Caries - Predictor Of Carious Activity In Permanent Dentition - Laura Maria Gavrilescu; Marinela Pasareanu; Vasilica Toma; Eugeniu Mihalas; Cristiana Dana Maxim (Romanian Society of Oral Rehabilitation, 2013)
Aim of the study is the optimisation of the child's dental management, especially regarding the health and odonto-periodontal integrity of mixed dentition. Materials and methods We performed a clinical and paraclinical population based study from the point of view of carious activity in mixed dentition on a lot of 212 subjects with the ages between 6 and 12 years, from urban and rural areas of Bacau and Iasi. Results In 84.32% of cases the dmft >0, in 50.98% exists an association with DMFT >0. Low frequency of tooth brushing associated with dmft >0, lead to an increased risk of caries in permanent dentition. In the studied lot most children admit eating sweets (86.79%), of which 65.21% have over two snacks a day between main meals. Conclusions It is considered that clinical variables associated with consumption of carbohydrates or with Streptococcus mutans and Lactobacillus acidophilus presence or with low frequency of tooth brushing can be relevant predictors for the occurrence of dental caries in mixed dentition and permanent dentition.